The Preaching of the Young Indonesian Dai Association (IDMI) in Realizing Religious Moderation among the Young Generation in Bantaeng Regency - Isnaeni; Abdul Rasyid Masri; Sakaruddin (Jurnal Mercusuar, 2023)
The aim of this research is to analyze the preaching activities of the Indonesian Young Preachers Association (IDMI) in promoting religious moderation among the youth in Bantaeng Regency. The study employs a qualitative approach with library research focusing on the preaching activities of IDMI in promoting religious moderation among the youth in Bantaeng Regency. The methods of data collection include interviews, observations, and documentation. The findings indicate that IDMI is committed to promoting religious moderation among the youth in Bantaeng Regency, aligned with its vision and mission of creating a religious, peaceful, and optimistically moderate society within the framework of the unitary state of Indonesia. Solidarity among IDMI members is highly valued, with a commitment to maintaining harmony within the organization and welcoming individuals from diverse backgrounds except those with extremist ideologies. IDMI serves as a platform in Bantaeng Regency for preachers to join regardless of their backgrounds, fostering organizational harmony and providing opportunities for skill development. The mission of IDMI, focusing on promoting religious moderation, contributes to nation-building by emphasizing preaching, education, and understanding related to the unity of the Indonesian state, including Quranic and Hadith studies and understanding the principles of the Indonesian state.